Disparities in the "who" and "where" of the vehicle purchase decision-making process for lower-income households. (April 2023) - Pierce, Gregory; Connolly, Rachel
Highlights: Evidence on sociodemographic drivers affecting household vehicle search is limited. Data from a representative survey of low- and moderate-income households was used. Sex and race influence who makes primary vehicle purchase decisions. Education, income, and age affect whether a vehicle is bought from a formal seller. Findings reflect broader regressive differences in intra-household decision-making. Abstract: The completion of a vehicle purchase is a major decision point which presents substantial financial implications for low-income households. As compared to the expansive bodies of literature on the low-income housing search and the relationship between travel behavior constraints and intra-household race and sex/gender dynamics, literature on the sociodemographic drivers influencing the vehicle search and purchase process for low-income households is scant. We begin to fill these knowledge gaps by analyzing data on major decision-making aspects of vehicle purchase from a representative survey of 1, 604 low- and moderate-income households in California, where vehicle ownership and dependence among low-income households is high. We find that sex/gender and race or ethnicity both influence who within a household is the reported primary-decision maker in vehicle purchase searches, with Hispanic and Asian females being significantly less likely to be described as the primary decision-maker in their households' processes. More educated, higher income and older respondents were also more likely to purchase a vehicle from a traditional automobile dealer rather than an online seller or other informal source. These findings reflect broader, regressive differences in intra-household financial decision-making as well as inequitable disparities in the purchase process. The results also present implications for lower-income household financial management, and a growing field of policymaking aimed to support a just transition in clean vehicle adoption.